The Complement and Coagulation Cascades Pathway is Associated with Acute Necrotizing Pancreatitis by Genomics and Proteomics Analysis - Zhang X; Li Z; Liu W; Du J; Liu Y; Yu N; Liu C; Zeng M; Zhang XM (Dove Medical Press, 2022)
Xinyu Zhang,1,* Zenghui Li,1,* Wei Liu,1 Juanjuan Du,1 Yun Liu,2 Ningjun Yu,1 Chao Liu,1 Mei Zeng,3 Xiaoming Zhang1 1Medical Imaging Key Laboratory of Sichuan Province and Department of Radiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, 637000, People's Republic of China; 2Department of Forensic Medicine, North Sichuan Medical College, Nanchong, Sichuan, 637000, People's Republic of China; 3Institute of Rheumatology and Immunology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, 637000, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoming Zhang, Medical Imaging Key Laboratory of Sichuan Province and Department of Radiology, Affiliated Hospital of North Sichuan Medical College, No.1 South Maoyuan Road, Nanchong, Sichuan, 637000, People's Republic of China, Tel +86 13808271001, Email zhangxm@nsmc.edu.cn Mei Zeng, Institute of Rheumatology and Immunology, Affiliated Hospital of North Sichuan Medical College, 63 # Wenhua Road, Nanchong, Sichuan, 637000, People's Republic of China, Tel +86 13990807850, Email zengmei123@gmail.comPurpose: Acute pancreatitis can be classified histologically as interstitial edema pancreatitis (IEP) or as acute necrotizing pancreatitis (ANP). ANP has a higher mortality and long-term or short-term sequelae than IEP. Therefore, this work aims to explore the differences in pathogenesis between ANP and IEP and it has great clinical importance for the treatment and prevention of ANP.Methods: In this work, whole blood samples from IEP and ANP patients were analyzed by whole gene sequencing (WGS). Serum samples from IEP and ANP patients were evaluated via enzyme-linked immunosorbent assay (ELISA). Meanwhile, pancreatic tissues of IEP and ANP rat models were subjected to data independent acquisition (DIA) proteomics assays. Then, the WGS analysis and DIA proteomics assay data were analyzed comprehensively.Results: Six pathways were found to be significantly different in the ANP/IEP groups through WGS analysis. DIA proteomics found eleven different pathways. In both assays, the complement and coagulation cascades pathway was the most significantly different (p < 0.01) pathway between the two groups. WGS analysis showed base mutations in ten genes in the complement and coagulation cascades pathway. These results were consistent with the ten proteins detected by DIA proteomics analysis, which were significantly upregulated in the ANP/IEP groups. In addition, five of these proteins, complement C3, complement Factor I, alpha-2-macroglobulin, complement C9, and serpin family C member 1, were successfully verified by parallel reaction monitoring analysis and ELISA.Conclusion: C3, CFI, A2m, C9, and Serpinc1, which belong to complement and coagulation cascades pathway, may promote pancreatic necrosis and aggravate the severity of ANP.Keywords: acute necrotizing pancreatitis, complement and coagulation cascades pathway, data independent acquisition proteomics, interstitial edema pancreatitis, whole gene sequencing genomics